2021
DOI: 10.1145/3479525
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Deplatforming as a Moderation Strategy on Twitter

Abstract: Deplatforming refers to the permanent ban of controversial public figures with large followings on social media sites. In recent years, platforms like Facebook, Twitter and YouTube have deplatformed many influencers to curb the spread of offensive speech. We present a case study of three high-profile influencers who were deplatformed on Twitter---Alex Jones, Milo Yiannopoulos, and Owen Benjamin. Working with over 49M tweets, we found that deplatforming significantly reduced the number of conversations about al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 48 publications
0
84
0
1
Order By: Relevance
“…While most researchers have tracked the activities of banned community members after [2,28,43,54,56,57,60] the ban or right before the ban [13], our analysis goes earlier in the existence of these communities to show that the majority of the Q-users likely joined Reddit to engage in and focus on QAnon-related activities. This finding extends our understanding of conspiracist behavior on Reddit, and provides a recommendation for future works to study the other aspects of the participation of active members prior to the creation of the later-banned communities, or in parallel to their activities there.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While most researchers have tracked the activities of banned community members after [2,28,43,54,56,57,60] the ban or right before the ban [13], our analysis goes earlier in the existence of these communities to show that the majority of the Q-users likely joined Reddit to engage in and focus on QAnon-related activities. This finding extends our understanding of conspiracist behavior on Reddit, and provides a recommendation for future works to study the other aspects of the participation of active members prior to the creation of the later-banned communities, or in parallel to their activities there.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…The effectiveness of deplatforming. Prior work has shown that for social media websites, deplatforming is a powerful tool to reduce harmful behaviors on the platform [13,28,60]. However, users or communities that were deplatformed might move to alternative platforms [54,57] and engage in more toxic behaviors [2,55].…”
Section: Background and Related Workmentioning
confidence: 99%
“…As seen in Table 3, the selected thresholds of values for identifying focus profiles lead to a small number of such profiles in all clusters, compared to the size of the 3T dataset. This can be attributed to the following reasons: a) to start with, the number of toxic tweets on Twitter is expected to be gen-erally small (∟8% was reported by Founta et al (2018)); b) then, extremely toxic profiles do not last long on Twitter: they get reported for misconduct violation and are banned fairly quickly (Jhaver et al 2021); c) our selected thresholds are conservative (min median=0.4 and max Gini=0.25) and applied in a combined fashion, as we aim to identify extreme cases of both highly toxic profiles, who are also consistent in their toxicity (not just sporadically toxic).…”
Section: Twitter Profile Clusteringmentioning
confidence: 99%
“…As per Grimmelmann's taxonomy of online moderation, banning is one of the four key techniques that moderators can adopt to avoid disruptions caused by malicious actors [12,19]. Several studies have focused on understanding the impact of bans and deplatforming -be it at an individual level [8,18], communitylevel (mass removal of xenophobic communities) [7,20,30,31,41], or platform level (banning of right-wing platforms like Parler from Google's app store) [2,3]. These studies find that while bans and deplatforming force a large fraction of users to abandon the platform, a few users and communities evade the ban and continue malicious activities that cause sustained issues relating to abuse, propaganda, and sometimes even leading to real-life acts of violence.…”
Section: Banning and Deplatformingmentioning
confidence: 99%